Disclosure of HIV Status to Perinatally Infected Adolescents in Urban Uganda: A Qualitative Study on Timing, Process, and Outcomes. (July 2015) - Mutumba, Massy; Musiime, Victor; Tsai, Alexander C.; Byaruhanga, Judith; Kiweewa, Francis; Bauermeister, José A.; Snow, Rachel C.
Abstract : N/A: Disclosure of HIV status to children and adolescents living with HIV remains a challenge in pediatric HIV care. Many of the current disclosure guidelines from national and international bodies recommend that perinatally infected children be informed of their HIV status prior to adolescence, but rates of disclosure in both high‐ and low‐income countries remains low. The applicability of the recommendations to low‐income countries remains largely unknown, as few studies have explored the disclosure process in these settings. Our purpose was to explore disclosure experiences of HIV‐infected adolescents in Uganda. Disclosure was a largely one‐time event conducted by health care providers. The average age at disclosure was 13 years. Disclosure elicited a diverse array of positive and negative reactions, including suicidal ideation; reactions were closely associated with participant age, gender, knowledge about HIV, and health status at time of disclosure. Interventions to promote locally effective, process‐oriented approaches to early disclosure are needed.